Broad ligament ectopic pregnancy: a dilemma to diagnose - Saxena, Namrata; Bansal, Neeta; Singhal, Pradeep; Ramola, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Broad ligament ectopic pregnancy is a rare and serious form of extrauterine pregnancy with a high risk of maternal mortality. There are no specific clinical features. Ultrasonography may help in diagnosis, but definitive diagnosis is made only during surgery. Authors are reporting a case of 30 years female G3P1L1A1 seven weeks pregnancy with previous lower segment cesarean section and previous history of right sided salpingectomy with no complaints. Ultrasound was advised to know the location of sac this time, in which, she was diagnosed as a case right sided unruptured live ovarian ectopic pregnancy. On examination, signs and symptoms of ectopic pregnancy were absent. On laparoscopy, she was diagnosed as a case of right sided live unruptured broad ligament ectopic pregnancy as her right ovary was absent because of previous surgery. With advances in sonography and laparoscopic skills, more cases can be diagnosed in the first trimester and can be safely managed laparoscopically.